Contribution to the knowledge of the genus Harpalus in China, with description of new taxa (Coleoptera: Carabidae: Harpalini) - Kataev, Boris M.; Liang, Hongbin (Zootaxa, 2007)
The paper deals with the taxonomy of six Palaearctic species of the genus Harpalus Latreille, 1802, two of which are described as new, from China: H. vernicosus sp. n. (Sichuan and Tibet) and H. parasinuatus sp. n. (Sichuan and Qinghai). Three species (H. viridanus Motschulsky, 1844, H. kaznakovi Kataev & Wrase, 1997, and H. giacomazzoi Kataev & Wrase, 1996) are treated as polytypic and three new subspecies are described from China: H. viridanus angustibasis ssp. n. (Qinghai, Tibet, and Sichuan), H. kaznakovi lilliputa ssp. n. (Tibet), and H. giacomazzoi gracilis ssp. n. (Tibet). H. viridanus staudingerianus Schauberger, 1932, stat. rest., which was formerly synonymized with H. viridanus, is treated as a separate subspecies from southernmost Gansu. New data about the distribution of H. potanini Tschitschérine, 1906 are provided and the taxonomic position of this species is discussed. Lectotypes are designated for H. przewalskyi Tschitschérine, 1894 (the former designation of the lectotype of this taxon by Kataev in 1989 is invalid), H. fuscipalpis var. versicolor Reitter, 1900 and H. potanini Tschitschérine, 1906.